2019
DOI: 10.1002/csr.1725
|View full text |Cite
|
Sign up to set email alerts
|

When are internal and external corporate social responsibility initiatives amplified? Employee engagement in corporate social responsibility initiatives on prosocial and proactive behaviors

Abstract: The aim of the study is to test not only the relative importance effect of employees' external and internal corporate social responsibility (CSR) perceptions on prosocial and proactive behaviors (i.e., organizational citizenship behavior [OCB] and job crafting) but also the impact of the interaction of these two kinds of employee CSR perceptions on proactive behaviors. Survey-based data were collected from 181 employees at eight luxury hotels located in South Korea. Using a two-wave longitudinal design, we mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 63 publications
(110 reference statements)
6
100
0
1
Order By: Relevance
“…The recent CSR trends have shifted organization's orientation from earning profit and improving its corporate image (Reverte, ) to exploring environmental, economic, social, ethical, legal, and discretionary responsibilities of the organizations (Fifka & Berg, ). Recently, research studies have shifted focus from macro‐level to micro‐level effects of CSR (Glavas ), by attending to the fact that how CSR influences the attitudes and behaviors of employees (Hur, Moon, & Choi, ; Lee & Chen, ; Testa, Boiral, & Heras‐Saizarbitoria, ).…”
Section: Introductionmentioning
confidence: 99%
“…The recent CSR trends have shifted organization's orientation from earning profit and improving its corporate image (Reverte, ) to exploring environmental, economic, social, ethical, legal, and discretionary responsibilities of the organizations (Fifka & Berg, ). Recently, research studies have shifted focus from macro‐level to micro‐level effects of CSR (Glavas ), by attending to the fact that how CSR influences the attitudes and behaviors of employees (Hur, Moon, & Choi, ; Lee & Chen, ; Testa, Boiral, & Heras‐Saizarbitoria, ).…”
Section: Introductionmentioning
confidence: 99%
“…In previous tourism and hospitality studies, the linkage between CSR perception and OCB was investigated (Fu et al, 2014; He, Zhang, & Morrison, 2019; Hur et al, 2019; Kim et al, 2017; Raub & Blunschi, 2014). Analyzing data from 211 hotel employees in United‐Kingdom, Raub and Blunschi (2014) indicated that employees' CSR awareness contributes helping behavior, voice behavior, and personal initiative both directly and indirectly through task significance.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Within micro level CSR studies, mostly customers (García de Leaniz & Del Bosque Rodríguez, 2015; González‐Rodríguez & Díaz‐Fernández, 2020; Swimberghe & Wooldridge, 2014; Yin, Du, & Chen, 2020), qualified prospective employees (Boğan & Dedeoğlu, 2019a; Horng, Hsu, & Tsai, 2019), local people (Su et al, 2017; Lee, Kim, & Kim, 2018; Gursoy, Boğan, Dedeoğlu, & Çalışkan, 2019) and incumbent employees' responses to CSR practices are investigated. Extant studies have shown a positive relationship between hospitality employees' CSR perceptions and various employee outcomes such as affective organizational commitment (Wong & Gao, 2014), organizational identification (Cheema, Afsar, Al‐Ghazali, & Maqsoom, 2020; Park & Levy, 2014), employee volunteerism (Afridi et al, 2020), work engagement (Gürlek & Tuna, 2019), job satisfaction (Appiah, 2019; Boğan, Türkay, & Dedeoğlu, 2018), authenticity (Afridi et al, 2020), organizational citizenship behavior (Hur, Moon, & Choi, 2019; Kim, Rhou, Uysal, & Kwon, 2017), trust in organization (Boğan & Dedeoğlu, 2019b) pro‐environmental behavior (Cheema et al, 2020), job crafting (Hur et al, 2019), and innovative work behavior (Afridi et al, 2020). However, it is stated that employees' perceptions of CSR is “still an under‐researched area” in hospitality industry (Ko, Chan, & Wong, 2019, p. 1879).…”
Section: Introductionmentioning
confidence: 99%
“…It is a sad latitude that use of technology may cut the jobs in firm's heterogeneity (Canova, Lopez-Salido, & Michelacci, 2007;Uysal, Yotov, & Zylkin, 2015); therefore, the impact of software implementation becomes important in human life. Linkage of internal CSR with external CSR has differential effects on perceptional and prosocial behaviors (Hur, Moon, & Choi, 2019). Because this raises question on internal CSR, there is the need of research to investigate how motivation and feeling of job insecurity will be influenced by the intentions of companies for technological shift.…”
Section: Problem Statementmentioning
confidence: 99%